Obstetrics By Ten Teachers - Campbell, Stuart; Lees, Christoph (London : Arnold ; Distributed in the Americas by Little Brown, 2000)
Revised in line with curriculum changes, this text integrates basic sciences and clinical material, to offer a logical approach to diagnosis and treatment. Separate chapters cover subjects such as obstetric emergencies, imaging, neonatology, and emotional and psychiatric changes in pregnancy.
Includes index
Bibliography: page 350
Keywords: Obstetrics; Pregnancy